Prenatal diagnosis of corpus callosum agenesis by 3D volumetric neurosonography: a new alternative for evaluation of midline brain anomalies - Albinagorta Olórtegui, Roberto (2014)
Agenesis of corpus callosum (ACC) is a central nervous system fetal anomaly of variable outcome; prenatal diagnosis is difficult due to the limitations of conventional ultrasound such as difficult visualization of the corpus callosum and obtaining adequate planes. Diagnosis is suspected on indirect signs and must be confirmed by neurosonography. 3D evaluation offers some advantages in fetal brain examination; the volume obtained allows generation of multiple planes that optimize the neurosonography study. We present a case of prenatal diagnosis of a fetus with ACC performed by 3D volumetric neurosonography and its role as new alternative for midline brain anomalies evaluation.Keywords: Corpus callosum agenesis, neurosonography, 3D ultrasound, brain midline.